PERANCANGAN SISTEM KEAMANAN SEPEDA MOTOR DENGAN RFID DI JURUSAN TSM SMKN 1 TIRTAJAYA - Zulfikar, Fikri; Anas, Ahmad (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2022)
As motorcycles become more popular in Indonesia, more and more“vocational high schools are offering a core course in motorcycle technique (TSM) in addition to life skills training. They also want their students to become entrepreneurs. This study hopes to provide entrepreneurial opportunities to all his TSM students especially in his SMKN 1 Tirtajaya. This research focuses on motorcycle security based on RFID and Arduino Uno. With motorcycle thefts on the rise at the moment and the high cost of motorcycle security equipment, this study will reduce motorcycle theft crimes and provide entrepreneurial opportunities for students after the completion of SMKN 1 Tirtajaya.”